Characterization of patients with diabetes who were incidentally found to be glutamic acid decarboxylase autoantibody‐positive by bridging‐type enzyme‐linked immunosorbent assay - Eiji Kawasaki; Takahiro Fukuyama; Aira Uchida; Yoko Sagara; Hidekazu Tamai; Yuko Nakano; Masayuki Tojikubo; Yuji Hiromatsu; Nobuhiko Koga (Journal of Diabetes Investigation, 2020)
Abstract This study aimed to characterize diabetic patients incidentally found to be positive for glutamic acid decarboxylase autoantibodies (GADA) in general practice. Using bridging‐type enzyme‐linked immunosorbent assay, we screened 1,040 patients with phenotypic type 2 diabetes for GADA, finding 25 (2.4%) to be positive. However, on retesting, with a median interval of 19 days, 44% of GADA‐positive patients turned negative (Disappearing Group). The mean age at diabetes onset was significantly higher (P < 0.05) and GADA titers at first determination were significantly lower (P < 0.001) in the Disappearing Group compared with the Persistent Positive Group. On initial screening, all patients in the Disappearing Group had GADA titers of <6.5 U/mL. The current study showed that a portion of phenotypic type 2 diabetic patients incidentally identified as GADA‐positive were falsely positive, and that to avoid the misclassification, remeasurement of GADA is essential in cases showing very low titers.